KONTRIBUSI IBU RUMAH TANGGA TERHADAP PENDAPATAN KELUARGA TANI DI DESA POOPO SELATAN KECAMATAN PASSI TIMUR KABUPATEN BOLAANG MONGONDOW (Housewives Contribution to Farming Family Income in South Poopo Village East Passi District, Bolaang Mongondow Regency) - Martha Anastassya Sondakh; Charles R. Ngangi; Jelly R. D. Lumingkewas (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2022)
This study aims to analyze the contribution of housewives to the income of farming families in South Poopo Village, East Passi District, Bolaang Mongondow Regency. The research was carried out from October to December 2021. The data used were primary and secondary data. Data analysis wasÂ done descriptively. The results showed that the contribution of housewives to the income of farming families in South Poopo Village was included in the small category. Tthis could be seen from the value of the contribution that was generated, which was only 29.35%.